In search of our human face: Black consciousness, black spirituality, inclusive humanity and the politics of vulgarity - Boesak, Allan (HTS teologiese studies, 2020)
This contribution grapples with the question: Is there a relationship between Steve Biko’s ‘quest for a true humanity’ or, differently put, his search for South Africa’s ‘human face’ and Vuyani Vellem’s quest for an African spirituality? Our proposition is that there is such a relationship. This discussion is framed overall by two other questions: What is the relevance of this ‘quest’ within the present South African context, what is its contribution to the global situation and, fundamentally, what is the contribution black liberation theology can make to these discourses? In the course of this exploration, we engage the concepts of Africanisation and Afrocentricity, colonisation, coloniality and decoloniality, and we ask whether a true Afro-pluralism is possible without a true African indigeneity. These concepts, we shall argue, are tools of struggle, not only in confronting colonisation and coloniality but also in battling imperialism, in the form I discuss here: the politics of vulgarity. I contend that an African spirituality, Biko’s ‘gift’ from Africa to the world, is the most appropriate vessel for that very gift.Contribution: This article serves as commemoration of the contribution the late Professor Vuyani Vellem made to the qualitative substantiation of black theology liberation in South Africa. It demonstrates the powerful way in which Afro-pluralism enhances the contra-narrative of imperialism and colonialism.